2018
DOI: 10.4314/jae.v22i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Information seeking behaviour of grass root level extension workers of the Department of Agricultural Extension in Bangladesh

Abstract: This study assessed the information searching behaviour of root level extension workers (SAAOs) to explore the relationships between the selected characteristics of the root level extension workers and their information searching behaviour. Chawgacha, Jhikargacha and Jessore Sadar upazila under Jessore district were the study area. All the 70 Sub Assistant Agriculture Officers (SAAOs) in these three upazilas participated in the study. The study revealed that 64.30%of the respondents were frequent information s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…As a result, low educated growers required high training need. Similar findings were reported by Hossain [20] and Olorunfemi et al [29].…”
Section: Relationship Between the Selected Characteristics Of The Pin...supporting
confidence: 91%
See 2 more Smart Citations
“…As a result, low educated growers required high training need. Similar findings were reported by Hossain [20] and Olorunfemi et al [29].…”
Section: Relationship Between the Selected Characteristics Of The Pin...supporting
confidence: 91%
“…Kshash [16] reported similar findings in his study. Hossain [20] found that "the majority (about 82%) of the potato farmers had medium to high training need in his study area". Yeasmin et al [21] reported that "almost 99% of fish farmers had medium to high training need in their study area".…”
Section: Overall Training Need Of the Pineapple Growersmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition is supported by the results of a study by Enwelu, Enwereuzor, Asadu, Nwalieji, & Ugwuoke, (2017) that extension workers' access to information and extension skills in using information and communication technology (ICT) are still inadequate. Satisfaction with the work of an extension worker is positively related to information seeking (Hossain, Azad, Al Mufthi, Alam, & Abdullah, 2018). Another factor, which also affects the role of agricultural extension workers, is that the number of extension workers is inadequate compared to the area served.…”
Section: Figure 1 Relationship Between Research Variablesmentioning
confidence: 99%